The Future of Tamaulipas MSMEs after COVID-19: Intention to Adopt Inbound Marketing Tools - Müller-Pérez, Jessica (2022)
Since the emergence of COVID-19, the interruption of non-core activities negatively affected the entire world economy so that companies in emerging countries had to adapt to the “new reality” by seeking new business alternatives. The objective of this study is to determine the intention of Tamaulipas MSMEs to adopt inbound marketing tools based on the Technology Acceptance Model (TAM), considering the variables of attitudes, trust, and perceived technological risk. The proposed model was analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. A sample of 310 companies from the state of Tamaulipas was obtained. The results showed that perceived usefulness, trust, attitude, and word of mouth (WOM), were the variables that most influence the intention to adopt inbound marketing tools and, on the contrary, perceived ease and perceived risk were not significant. This demonstrates that adding new variables to the TAM model improves the predictive power of intention with respect to the adoption of new technology, providing a picture of the behavior of companies seeking to continue growing, despite the lags left by the COVID-19 pandemic.